Association between anaerobic and aerobic capacities by different of race strategy in athletics 400m running - Oshiden, M.; Hasegawa, N.; Fujie, S.; Horii, N.; Iemitsu, M. (The Journal of Physical Fitness and Sports Medicine, 2017)
[Aims] The 400m track race is longest in the sprint race, the 400m sprinter need to both of anaerobic and aerobic exercise capacities to maintain higher speed. In the 400m sprinter, there are sprinter types of "first half type" in which the running speed in the first half section is high and "even type" in which the running speed in the whole race is almost unchanged. However, the requirement of exercise capacity may be differed between these types. The purpose of this study is to investigate whether a different of race strategy affects the relationship between the performance of 400m running and anaerobic and aerobic exercise capacities. [Methods] Thirty-two 400m or 400m hurdle sprinters (18-21 years, male; n=23, female; n=9) participated in this study. The mean power output during the 30 seconds of a Wingate test was measured as an anaerobic exercise capacity. The maximal oxygen uptake (VO2max) was measured as an aerobic exercise capacity. The 400m race season's best time (400mSB) and the race strategy questionnaire in each sprinter. [Results] Significant negative correlation between anaerobic capacity and 400SB was found (r=-0.78, p<0.01), but was not significantly correlated between VO2max and 400SB. In eithef "first half type" and "even type" sprinters, anaerobic capacity was negatively correlated with 400SB (r=-0.76, p<0.01 and r=-0.80, p<0.01 respectively). [Conclusions] These results suggest that the anaerobic capacity may be involved in the performance of 400m race, and this relationship was similar even if race strategy was different type.